-(x+3)=5x-9

Simple and best practice solution for -(x+3)=5x-9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(x+3)=5x-9 equation:


Simplifying
-1(x + 3) = 5x + -9

Reorder the terms:
-1(3 + x) = 5x + -9
(3 * -1 + x * -1) = 5x + -9
(-3 + -1x) = 5x + -9

Reorder the terms:
-3 + -1x = -9 + 5x

Solving
-3 + -1x = -9 + 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.
-3 + -1x + -5x = -9 + 5x + -5x

Combine like terms: -1x + -5x = -6x
-3 + -6x = -9 + 5x + -5x

Combine like terms: 5x + -5x = 0
-3 + -6x = -9 + 0
-3 + -6x = -9

Add '3' to each side of the equation.
-3 + 3 + -6x = -9 + 3

Combine like terms: -3 + 3 = 0
0 + -6x = -9 + 3
-6x = -9 + 3

Combine like terms: -9 + 3 = -6
-6x = -6

Divide each side by '-6'.
x = 1

Simplifying
x = 1

See similar equations:

| 2(a-6)=-9 | | 4x^2+10x+256=0 | | 8-6(6+8p)=-8p+12 | | 4b+56=64 | | 35r^2+ry-5xr-2xy= | | x+11x-151=101 | | 3m^3+24p^3=0 | | 6x-5=5x+10 | | 12r+(-12)= | | 6+2x-3=4x+2 | | 10m-23=27 | | r(9r+1)=8 | | 3+6x-3x=7+3x-6x | | 3+6x-3x=7+6x-3x | | -x+1=x-1 | | y=-2b+7mx | | -48+11x-8x=36 | | K^2-6=5k | | 5x+12x-123=132 | | 20r^2+25ry-4xr-5xy= | | X=6r^2+17r-45 | | X(5x+7)=17 | | 15x-2(4x+1)=-9 | | 0=2000+25t | | 10(p+2)+16(-3-p)= | | (3x-14)+(7x-6)=50 | | 7x+3x-125=115 | | 4(4)-5y=23 | | 4x+x^2+4=0 | | 4x-5(-3)=23 | | 4(v-8)=7v-2 | | 3m+1-1m=-7+3m-1+1 |

Equations solver categories